Taguchi-Based Experimental Investigation of Heat Transfer from an Impinging Jet to a Rotating Cylinder - Pusat, Gongur; Sahinaslan, Abdulmuttalip; Kistak, Celal; Celik, Nevin (Mdpi, 2025)
In this study, the design and optimization of some parameters thought to be effective in the convective heat transfer caused by an air jet impinging on a rotating heated cylindrical surface are investigated by using the Taguchi optimization method. The temperature distribution on the rotating cylindrical surface resulting from air jet impingement is measured with an infrared thermal camera, and the heat transfer due to the difference between the air jet temperature and the surface temperature is shown by Nusselt number. The effects of some major parameters such as the Reynolds number of the air jet, jet-to-surface distance, speed of the rotating cylinder, geometry of the nozzle, and constant surface temperature on Nusselt number are evaluated by means of Analysis of Variance (ANOVA). As a result, the Reynolds number, surface temperature, and rotational speed are found to play key roles in enhancing heat transfer under the tested conditions. The results provide valuable insight for thermal management applications such as gas turbines, brake disks, and electronic cooling, and the adopted Taguchi-based approach may serve as a systematic framework for future studies involving nanofluids and multi-jet systems.
Keywords: jet impingement cooling; rotating cylindrical surfaces; heat transfer enhancement; Taguchi method